The effectiveness of the “COVID19 Origin Response and Resilience Initiative (CORRI)” program involving private sector in Humbang Hasundutan District, North Sumatera - Sitorus, Syafriana (Berita Kedokteran Masyarakat, 2021)
Objective: This study examines the effectiveness of the “COVID19 Origin Response and Resilience Initiative (CORRI)” program involving private sector in Humbang Hasundutan District, North Sumatera. Content: The CORRI Program had been conducted for a year (2020-2021) in Humbang Hasundutan Regency. The main target of this activity was vulnerable groups, especially coffee farmers (the majority of people’s livelihoods). During the COVID-19 pandemic, there was not the involvement of the private sector. The government, through BPBD, was working hard to prevent local transmission of Covid19 because this region had a high potential for Covid19 cases because the activities for transaction market and tourism sectors. The results of the evaluation showed that (a) people who accessed hand wash facilities reached 13,643 people and it could increase significantly community knowledge and awareness of hand washing, (b) It reached 1000 heads of households who received hygiene kits, and (c) fulfilment of communication and information media In strategic places, including health facilities, which 3,132 people reached out to the media, including billboards, banners, posters, leaflets and others. This study could describe that the government needed to cooperate with private sectors for preventing the occurrence of Covid19 transmission. In other hands, it could be applied in other areas (by using local wisdom). The implementation of this program had received support from the local government and district task forces in sustainability program.